2003
DOI: 10.1046/j.1365-3156.2003.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of subacute sclerosing panencephalitis in Papua New Guinea

Abstract: Summary Eighty‐three children presented at Goroka Base Hospital in the Eastern Highlands Province (EHP) of Papua New Guinea over a period of 3 years and 9 months between February 1997 and November 2000 were confirmed to have subacute sclerosing panencephalitis (SSPE). Confirmation of the diagnosis was based on the demonstration of high titres of measles antibodies in the cerebrospinal fluid and/or serum in association with clinical features supportive of SSPE, including characteristic electroencephalographic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Consistent with previously-reported studies [23], we could not always determine age of onset of symptoms accurately, but the median age at the time of admission in our children (7.3 years) and the male∶female ratio (1.4∶1) were similar to those in SSPE cases from the PNG highlands a decade ago (7.9 years and 1.2∶1, respectively) [4]. Although a male excess is usual, there has been a large age range at presentation, from <5 years in one of the first PNG studies [22] to >10 years in Europid populations [23], [24].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with previously-reported studies [23], we could not always determine age of onset of symptoms accurately, but the median age at the time of admission in our children (7.3 years) and the male∶female ratio (1.4∶1) were similar to those in SSPE cases from the PNG highlands a decade ago (7.9 years and 1.2∶1, respectively) [4]. Although a male excess is usual, there has been a large age range at presentation, from <5 years in one of the first PNG studies [22] to >10 years in Europid populations [23], [24].…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of SSPE in most countries is <5 per million population <20 years of age, although this figure can be higher in the developing world where vaccination programs are not fully established [4]. The first reports of an unusually high incidence in Papua New Guinea (PNG) were published in the early 1990's [5], with rates between 1988 and 1999 that varied from 13 [5] to 98 [6] per million population <20 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…14 In another study, the mean age of onset of SSPE was reported as 7.9 years. 15 In the present study, 12 SSPE patients (54.5%) were < 6 years old and 10 (45.5%) were ≥ 6 years old and the period between the beginning of complaints and The risk of SSPE in children < 1 year old is 16-times higher when compared with children who are > 5 years old and who have a history of measles. 16 In the present study, the mean age of having measles was only known for 7/10 children and was 2.12 years, and 10/22 children (45.5%) with SSPE had a history of measles while 6/22 children (27.3%) did not.…”
Section: Discussionmentioning
confidence: 44%
“…The ratio of males to females for measles infections in Japan was 1.1 to 1.3:1 from 1999 to 2007 and appears to be related to that for subacute sclerosing panencephalitis. In other countries, the ratio of males to females for subacute sclerosing panencephalitis was higher: 1.2:1 in Papua New Guinea (1997-2000), 18 1.9:1 in England and Wales (1990-2002), 19 2.6:1 in Bulgaria (1978-2002), 20 and 2.3:1 in Turkey (1995-1999). 21 However, there have been no reports of racial differences in subacute sclerosing panencephalitis.…”
Section: Discussionmentioning
confidence: 91%